Kritik Prinsip Keadilan Restoratif Terhadap Pasal 7 dan Pasal 9 Undang-Undang Nomor 11 Tahun 2012 Tentang Sistem Peradilan Pidana Anak Terhadap Pertanggungjawaban Pidana Anak Pelaku Perundungan - Rahmawati R (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the principle of restorative justice applied by law enforcement officers toward children as perpetrators of bullying, based on Articles 7 and 9 of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, and to examine effective guidance processes in preventing the recurrence of bullying from a restorative criminology perspective. This research is qualitative with a normative juridical approach. The research design is library research, reviewing legislation, legal doctrines, and relevant scholarly literature on restorative justice and the juvenile criminal justice system. The results indicate that the principle of restorative justice in Law Number 11 of 2012 is implemented through diversion mechanisms in Article 7 and community involvement in Article 9, aiming to restore relationships between child perpetrators of bullying, victims, and the social environment. These provisions emphasize the juvenile criminal justice system’s orientation toward non-repressive and participatory case resolution. However, they remain normative and procedural, lacking clear recovery indicators. Furthermore, the study finds that the implementation of Articles 7 and 9 does not fully align with restorative justice principles, as it does not ensure a balanced position between victims and perpetrators and provides minimal mechanisms for evaluating and supervising the continuity of recovery. Therefore, there is a need to strengthen regulations and guidelines for the substantive application of restorative justice so that the criminal accountability of child perpetrators of bullying is genuinely oriented toward recovery and the prevention of repeat offenses.